Ventral Midline Preputial Approach to the Caudal Abdomen in Male Dogs. Issue 6 (15th June 2016) - Daniel, Samson S.; Sardinas, Juan C.; Montavon, Pierre M.
Abstract : Objective: To describe a ventral midline preputial approach to the caudal abdominal cavity of male dogs. Study Design: Retrospective clinical study. Sample Population: Client‐owned dogs (n=12). Method: Medical records of dogs which underwent a ventral midline preputial approach to the caudal abdominal cavity were reviewed. The procedure, outcome, and complication were recorded. Results: Dogs underwent the preputial approach to the caudal abdominal cavity for various conditions. All dogs had an uneventful postoperative recovery and no major complications were recorded until suture removal at 10–14 days postoperative. Two dogs had minor complications treated conservatively which resolved. Conclusion: The use of ventral midline preputial approach is an option for access to the caudal abdomen. The approach preserves the protractor preputii muscles, obviates ligation of the branches of the caudal superficial epigastric vessels and eliminates the need for extensive subcutaneous dissection.